2010
DOI: 10.1161/circimaging.109.928663
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of 3D Echocardiographic Assessment of Left Ventricular Volumes, Mass, and Ejection Fraction in Neonates and Infants With Congenital Heart Disease

Abstract: Background-Quantitative assessment and validation of left ventricular (LV) volumes and mass in neonates and infantswith complex congenital heart disease (CHD) is important for clinical management but has not been undertaken. We compared matrix-array 3D echocardiography (3D echo) measurements of volumes, mass, and ejection fraction (EF) with those measured by cardiac MRI in young patients with CHD and small LVs because of either young age or LV hypoplasia. Methods and Results-Thirty-five patients aged Ͻ4 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 24 publications
4
65
0
2
Order By: Relevance
“…126 The use of 3D echocardiography has been validated for the measurement of RV volumes and EF, which correlated well with those variables determined by MRI imaging in a pediatric population. 127 Validation of 3D echocardiographic assessment in children with complex CHD, including a small LV, has been performed, 128 while sufficient data in children with PH are scant. A limitation of this method is that 3D echocardiography is dependent on adequate acoustic windows, which had been appropriate in only about 50% of all patients, 129 because of inadequate image quality.…”
Section: D Echocardiographymentioning
confidence: 99%
“…126 The use of 3D echocardiography has been validated for the measurement of RV volumes and EF, which correlated well with those variables determined by MRI imaging in a pediatric population. 127 Validation of 3D echocardiographic assessment in children with complex CHD, including a small LV, has been performed, 128 while sufficient data in children with PH are scant. A limitation of this method is that 3D echocardiography is dependent on adequate acoustic windows, which had been appropriate in only about 50% of all patients, 129 because of inadequate image quality.…”
Section: D Echocardiographymentioning
confidence: 99%
“…23,24 The role of LVM measurements by RT3DE in pediatric patients has been investigated less extensively, but some studies have revealed progress regarding accuracy, reproducibility, and efficiency in normal as well as abnormally shaped ventricles. 25,26 There is a need for pediatric reference values, because LVM changes during maturation. Currently, there are few valid pediatric normative data available.…”
mentioning
confidence: 99%
“…Since cardiac MRI may be challenging in some infants because of the need for sedation, possibly general anesthetic, and because breath-holding may be required, the accuracy of 3D echo allows a less-complex technique to be used in these very young patients. 6 …”
Section: Discussionmentioning
confidence: 99%